Realising advanced Enterprise system Affordances: A single-case study of a CRM-system implementation at a technology consultancy company - Antonsson, Oscar; Olsson, Sebastian (My University, 2022)
Enterprise systems offer organisations great action potentials (Affordances), however, getting employees to use the systems to their full potential is a lengthy process which is challenging for organisations. While previous studies have focused on strategic success factors from implementers point of view, less emphasis has been put on the perspective of users and how the envisioned affordances of the enterprise systems are actualised in practice. This thesis investigates what affordances implementers and users perceive in a technology and how certain variables affect users in realising the affordances of a technology. The thesis was conducted in the form of a qualitative single-case study of a technology consultancy company and the ongoing implementation of a Customer Relationship Management (CRM) system. Data was collected through semi-structured interviews with participants from the case company, observations, and internal documents and reports. Findings indicate that implementers and users at the case company had an overall similar understanding of what affordances the new CRM-system could offer. Four main affordances were identified, namely Single entry and access point, Aggregated view, Data driven actions, and Cross-collaboration. The realisation of these affordances followed a trajectory, creating different levels of affordances, meaning that the realisation of some affordances was dependent on the realisation of others. Further, the analysis identified twelve variables that influence users’ realisation of perceived affordances of the CRM-system, and these variables can explain difficulties experienced by the case company in the implementation. Five of the identified variables can be found in existing affordance theory literature while the remaining seven emerged from the data. Finally, the analysis indicated interrelations between variables and identified the reaching of a critical mass of users who feed the CRM-system with information as an essential steppingstone to realise the higher-level affordances of the system.
Keywords: Affordance theory; affordance actualisation; Customer relationship management; CRM-system; Enterprise system implementation; Technology adoption